Diabetic Retinopathy: Possibilities and Prospects for Retinoprotection - A. V. Malyshev; S. V. Yanchenko; E. N. Saverskaya; Sh. J. Teshaev; M. R. Avezova; I. I. Abdurahmonova; N. Saidova (Oftalʹmologiâ, 2024)
The article presents an analytical review of the literature on the possibilities of retinoprotective therapy (RPT) in patients with diabetic retinopathy (DR). The above data, on the one hand, confirm the clinical effectiveness of RPT based on the use of a complex of watersoluble polypeptide fractions of the retina in DR, and on the other, determine the need for further research in the framework of the problem under consideration. It seems relevant to conduct studies to assess the possibilities of using RPT in patients with minimal manifestations of DR (without visual signs of vascular changes), with DR in conditions of macular edema (against the background of anti-VEGF therapy and delayed laser coagulation of the retina), as well as in patients with proliferative DR after vitrectomy.